Formal Verification of a Peer-to-Peer Streaming Protocol - Ojo, Oluwafolake; Oluwatope, Ayodeji; Ajadi, Suraj (ScienceDirect, 2018)
Peer (P2P) networks have emerged as an efficient and affordable means of transmitting videos to numerous end-users via the Internet. The dynamic and heterogeneous nature of P2P streaming systems (P2PSS) makes testing, analyzing and verification a cumbersome task. However, formal methods offer efficient approaches to rigorously analyze and verify P2PSS. This paper demonstrates the use of formal verification techniques for analyzing the behavioral properties of P2PSS. We use temporal logics to analyze whether all the possible behaviors within the P2P streaming systems conform to the defined specifications. Specifically, we apply model checking to check the consistency, completeness and certainty of the model if the temporal properties of the proposed system satisfies the required specifications. Furthermore, the P2PSS framework was modeled and verified using Simulink Design Verifier (SDV) in MATLAB simulation tool. The simulations results showed 100% validation for all frames and 50% validation for I-frames prioritisation. Further, the probability of a peer capable of forwarding frames while receiving is at most 0.5.
Journal of King Saud University - Computer and Information Sciences Volume 32, Issue 6, July 2020, Pages 730-740
Keywords: Peer-to-peer networks; Video streaming and temporal logic; Obafemi Awolowo University; STEM